Ilegalismos, controle territorial armado e a cidade: reflexões na perspectiva de uma agenda de pesquisa - Hirata, Daniel; Rocha, Lia de Mattos; Santos Junior, Orlando Alves dos (Cadernos Metrópole, 2024)
DOI: https://doi.org/10.1590/2236-9996.2024-6168000-pt https://doi.org/10.1590/2236-9996.2024-6168000-en